2022
DOI: 10.1155/2022/8262304
|View full text |Cite
|
Sign up to set email alerts
|

Mix Method Approach of Measuring VR as a Pedagogical Tool to Enhance Experimental Learning: Motivation from Literature Survey of Previous Study

Abstract: This research has been experimented on our previous literature review. Technological advancement has prevailed in the modern era from the 20th century. Artificial intelligence and virtual worlds have been created for rapid technological development. This paper is aimed at exploring the effect of virtual reality as a pedagogical tool for enhancing experiential learning among undergraduate students. Considering this, it was a mixed-methods study following the design of sequential exploratory–which includes quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Implementing the educational and learning approach of constructivism helps to bridge the gap in the skilled workforce [133,134]. Moreover, the students, as learners, assert their experiences and become connected with the outside world [105], constructing a sustainable society [42], leading to sustainable employment generation and social empowerment in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing the educational and learning approach of constructivism helps to bridge the gap in the skilled workforce [133,134]. Moreover, the students, as learners, assert their experiences and become connected with the outside world [105], constructing a sustainable society [42], leading to sustainable employment generation and social empowerment in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…The science of gaining knowledge (through ETL) and developing understanding, leading to constructivism, has a combined impact on socio-cultural development [33]. The constructivism theory asserts experience-based constructive learning, which stresses the direct experi-ence of acquiring knowledge, in which students get involved with the world by applying their perspectives [105]. The social constructivism theory emphasizes the students' active learning, in which students as the learners build their knowledge in a particular social connectedness, along with cultural development with real-world situations [41].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…First, the immersion feature of VR/AR/MR can be helpful in improving learning efficiency since it allows learners to both mentally and emotionally engage in the simulated real-life situations [47,48]. In addition, since VR/AR/MR learning scenarios enable on-demand repetition, the immersive experiences can improve students' absorption and understanding of knowledge [46,49].…”
Section: Vr/ar/mr In Educationmentioning
confidence: 99%
“…ird, the engagement feature of VR/AR/MR, referring to "the extent to which a learner applies a level of attention and curiosity to a situation to achieve a desirable result" [46], has been found to increase happiness, motivation, and longterm dedication [49]. In a study conducted by Marks and omas [51], they found that 71.5% of subjects reported enhanced learning performance when they used VR/AR for the first time.…”
Section: Vr/ar/mr In Educationmentioning
confidence: 99%
“…Besides, a pedagogical experiment was also performed comprising of different steps, including pre-text, post-test, educational text, and questionnaire. This experiment is useful in determining the level of knowledge of the participants (Asad et al, 2022). Approximately 20 min were given to address the first section (pre-text), and overall 45 min to address other sections.…”
Section: Target Population and Sample Sizementioning
confidence: 99%